Decolorization of acid, disperse and reactive dyes by Trametes versicolor CBR43. Issue 9 (29th July 2017) - Yang, Seung-Ok; Sodaneath, Hong; Lee, Jung-In; Jung, Hyekyeng; Choi, Jin-Hee; Ryu, Hee Wook; Cho, Kyung-Suk
ABSTRACT: The mycoremediation has been considered as a promising method for decolorizing dye wastewater. To explore new bioresource for mycoremediation, a new white-rot fungus that could decolorize various dyes commonly used in textile industries was isolated, and its ligninolytic enzyme activity and decolorization capacity were characterized. The isolated CBR43 was identified as Trametes versicolor based on the morphological properties of its fruit body and spores, as well as through partial 18S rDNA gene sequences. Isolated CBR43 displayed high activities of laccase and Mn-dependent peroxidase, whereas its lignin peroxidase activity was relatively low. These ligninolytic enzyme activities in potato dextrose broth (PDB) medium were enhanced by the addition of yeast extract (1–10 g L −1 ). In particular, lignin peroxidase activity was increased more than 5 times in the PDB medium amended with 10 g L −1 of yeast extract. The CBR43 decolorized more than 90% of 200 mg L −1 acid dyes (red 114, blue 62 and black 172) and reactive dyes (red 120, blue 4, orange 16 and black 5) within 6 days in the PDB medium. CBR43 decolorized 67% of 200 mg L −1 acid orange 7 within 9 days. The decolorization efficiencies for disperse dyes (red 1, orange 3 and black 1) were 51–80% within 9 days. The CBR43 could effectively decolorize high concentrations of acid blue 62 and acid black 172 (500–700 mg L −1 ). The maximum dye decolorization rate was obtained at 28°C, pH 5, and 150 rpm in the PDB medium. T. versicolor CBR43 had high laccase and Mn-dependent peroxidase activities, and could decolorize a wide variety of dyes such as acid, disperse and reactive textile dyes. This fungus had decolorizing activities of azo-type dyes as well as anthraquinone-type dyes. T. versicolor CBR43 is one of promising bioresources for the decolorization of textile wastewater including various dyes.